Genetically predicted allergic rhinitis causally increases the risk of erectile dysfunction - Li, Peng; Meng, Zhaotun; Lin, Liqiang; Chen, Zhipeng; Lv, Huaiqing (Frontiers in Genetics, 2024)
Objective: Evidence shows that allergic rhinitis (AR) may increase the risk of erectile dysfunction (ED). This study aims to investigate whether there is a causal relationship between AAR and ED by mendelian randomization (MR) analysis. Methods: We performed a two-sample MR analysis using genome-wide association studies (GWAS) summary data. Single nucleotide polymorphisms (SNPs) associated with AR and ED were obtained from the GWAS database. The MR analysis primarily employed the inverse variance weighted (IVW), MR Egger, and weighted median (WM) methods. We assessed pleiotropy using the MR-PRESSO global test and MR-Egger regression. Cochran’s Q test was used to evaluate heterogeneity, and a leave-one-out analysis was performed to verify the robustness and reliability of the results. Results: The IVW analysis demonstrated a positive association between genetic susceptibility to AR and an elevated relative risk of ED (IVW OR = 1.40, P = 0.01, 95%CI 1.08-1.80). The results obtained from MR-Egger regression and WM methods exhibited a consistent trend with the results of the IVW method. Sensitivity analyses showed no evidence of heterogeneity nor horizontal pleiotropy. The leave-one-out analysis showed that the findings remained robust and were unaffected by any instrumental variables. Conclusion: This study presents genetic evidence that indicates a causal association between AR and ED.